The roots of American foreign policy an analysis of power and purpose - Kolko, Gabriel (Boston Beacon Press, 1969)
One of America's most perceptive young historians examines the misunderstood dimensions and implications of a great question confronting the nation -- our foreign policy. Professor Kolko makes it clear that our foreign policy is neither the result of omission or ignorance nor of a "military-industrial complex." Civilian authority and civilian-defined goals, he asserts, are the consistent sources of American foreign policy. From this premise, Kolko undertakes to investigate "the respectables," the self-styled liberal realists and businessman who are the architects of the decades-old premises of American foreign policy. He also outlines the nature of American power and interests in the modern world and provides an assessment of who gains and who loses as a result of the policies Washington pursues."-- BOOK JACKET.
Includes bibliographical references (pages 139-159) and index.
Keywords: United States -- Foreign relations -- 1945.